Ficción policial y memoria colectiva. El caso de Sangre kosher (2010) de María Inés Krimer (El Hilo de la Fabula, 2021)
The purpose of this article is to analyze the relationship between collective memory and detective literature in the novel Sangre kosher (2010), written by the Argentine author María Inés Krimer. The focus will be on the dialogue taking place between a socio-historical fact (the operations of Zwi Migdal procurers in Argentina at the beginning of the twentieth century) and the construction of a detective fiction. Firstly, the notion of collective memory in the literary field will be introduced; secondly, the genre characteristics of Sangre kosher are specified to discuss the elements it borrows from the subgenre of the historical detective novel, that is archival work and the construction of space. From there, the way in which this detective fiction uses these elements to build a purely enquire plot that relates the past and the present through the narrative voice of the first Jewish female detective in Argentinian literature is analyzed. Thus, the work analyzes the way that detective fiction contributes to Jewish collective memory.
Keywords: Collective memory; Historical police literature; Zwi Migdal; Ruth Epelbaum; Archival work; Space